Outbreak of hypernatremia, hyperthermia & azotemia during summer months among neonates admitted to tertiary care NICU and their immediate outcome - Dr. Manoj Donthamsetty; Dr. Manu C; Dr. Guruprasad (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Dehydration and hypernatremia amongst exclusively breast fed neonates due to inadequate breast feeding or due to less feeding is a potentially devastating condition, and its incidence rate increases during hot environment especially during summer months. We conducted this study to identify possible etiology behind dehydration and hypernatremia among healthy newborn. Methods: Hospital case records of 40 neonates admitted to the NICU in Bapuji Child Health Institute and Research Centre, Davangere during summer months (March –May) 2017 were retrospectively analysed. Case records were reviewed and data collected on parity of the mother, feeding practices,symptoms and signs at presentation, external environment temperature during the week prior to admission, biochemical changes and outcome. Results: During March-May 2017, there were 620 admissions in NICU. Amongst 620 cases, clinical profile, signs and symptoms, biochemical profile and outcome of 40 cases of hyperthermia were studied. 95% cases had significant weight loss (13-15%), 100% cases had hyperthermia (mean temp 99.3-101 F), 88% cases had hypernatremia (mean Na+ 155-185), 75% cases had azotemia (mean urea 96.73), creatinine(mean1.5). 95% cases were successfully treated according to NICU protocol and discharged within a short period but succumbed. Conclusion: Dehydration and hypernatremia is preventable and treatable condition. All the mothers need to taught correct feeding method like proper position and attachment of feeding. Signs of dehydration must be explained to mother as well as close relatives. Follow up visits should be ensured and check for weight is must. Not to encourage mother to give any other feed apart from exclusive breast feeding for first 6 months and even during summer months.